2015
DOI: 10.1093/ecco-jcc/jjv210
|View full text |Cite
|
Sign up to set email alerts
|

The Ulcerative Colitis Endoscopic Index of Severity More Accurately Reflects Clinical Outcomes and Long-term Prognosis than the Mayo Endoscopic Score

Abstract: Background and Aims: The Ulcerative Colitis Endoscopic Index of Severity (UCEIS) and the Mayo endoscopic score (Mayo ES) are used to evaluate ulcerative colitis (UC) severity. This study compared UCEIS and the Mayo ES for evaluating UC severity and outcomes in patients undergoing remission induction during routine clinical practice with the aim of predicting medium-to longterm prognosis. Methods: Forty-one UC patients who received colonoscopy before and after tacrolimus remission induction therapy were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 36 publications
4
118
0
2
Order By: Relevance
“…The severity of UC is often presented by clinical activity indices (CAI), which are described by several authors . Another, but complementary parameter is endoscopic index (EI), a true reflection of mucosal damage, or otherwise mucosal remission . In CD patients, the activity index (CDAI) is assessed by a different set of measurements .…”
Section: Introductionmentioning
confidence: 99%
“…The severity of UC is often presented by clinical activity indices (CAI), which are described by several authors . Another, but complementary parameter is endoscopic index (EI), a true reflection of mucosal damage, or otherwise mucosal remission . In CD patients, the activity index (CDAI) is assessed by a different set of measurements .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the more detailed scoring of the extent of ulcers compared to MES, UCIES includes the degree of vascular appearance. Indeed, it has been reported that UCEIS precisely reflects clinical outcomes and predicts the medium-to-long-term prognosis in UC patients on induction therapies [16]. However, only few studies have examined the association between fecal markers and UCEIS [17].…”
Section: Introductionmentioning
confidence: 99%
“…Usually at day 5-7 we complement repeat close clinical assessment with endoscopic re-evaluation. Not surprisingly, studies were able to correlate the endoscopic severity of disease with mid-term outcome [9,10], although most trials have used a later time point (e.g. 12 weeks) for reassessment.…”
Section: Short-term Control Of Response To Intensified Therapymentioning
confidence: 99%